Photoisomerization of Azobenzenes and Spirocompounds in Nematic and in Twisted Nematic Liquid Crystals - Bossi, Mariano Luis (2006)
Samples of a nematic mixture of ZLI1132 and of a twisted nematic mixture composed of ZLI1132 and chiral inductor S811, including 1%-10% (w/w) 4-N,N-dimethylaminoazobenzene (DAB), (4′-nitro)-4-N,Ndimethylaminoazobenzene (NDAB), spiropyran (SP), or spirooxazine (SO) were irradiated to produce the photochromic transformation of the dopant. The changes in the system were monitored by time-resolved transmission spectroscopy, time-resolved birefringence, or polarized Raman scattering. The medium sensitivity of the kinetics and spectroscopy of some of the probes was used to derive information on polarity of the medium. In the systems studied, apart from the changes in absorption spectrum, great changes in birefringence can be photoinduced and the order of the nematic phase can be changed in either direction, depending on the dopant. The open form of SP can discriminate orientation polarity. Although the polarity parallel to the mesogenic director is similar to that for acetone, the perpendicular orientation has a polarity similar to acetonitrile. In agreement with this observation, the kinetics of the Z f E isomerization of NDAB, oriented parallel to the mesogenic director, also experiences a polarity similar to that for acetone. The decay rate constant of the open form of SP displays a linear relationship between its Arrhenius parameters, which is universal in a great variety of homogeneous solvents, solvent mixtures, and liquid crystals, therefore validating the hypothesis that the same type of transformation is observed in all these cases, namely, the decay of the open form monomer. The dopants used have been proven to be adequate probes of bulklike properties in locally heterogeneous systems as liquid crystals.